Predictors and Complications of Post Kidney Transplant Leukopenia. (September 2021) - Vinson, Amanda; Teixeira, Alyne; Kiberd, Bryce; Tennankore, Karthik
Background: Leukopenia occurs frequently following kidney transplantation and is associated with adverse clinical outcomes including increased infectious risk. In this study we sought to characterize the causes and complications of leukopenia following kidney transplantation. Methods: In a cohort of adult patients (≥18 years) who underwent kidney transplant from Jan 2006-Dec 2017, we used univariable Cox proportional Hazards models to identify predictors of post-transplant leukopenia (WBC < 3500 mm 3 ). Factors associated with post-transplant leukopenia were then included in a multivariable backwards stepwise selection process to create a prediction model for the outcome of interest. Cox regression analyses were subsequently used to determine if post-transplant leukopenia was associated with complications. Results: Of 388 recipients, 152 (39%) developed posttransplant leukopenia. Factors associated with leukopenia included antithymocyte globulin as induction therapy (HR 3.32, 95% CI 2.25-4.91), valganciclovir (HR 1.84, 95% CI 1.25-2.70), tacrolimus (HR 3.05, 95% CI 1.08-8.55), prior blood transfusion (HR 1.17 per unit, 95% CI 1.09- 1.25), and donor age (HR 1.02 per year, 95% CI 1.00-1.03). Cytomegalovirus infection occurred in 26 patients with leukopenia (17.1%). Other than cytomegalovirus, leukopenia was not associated with posttransplant complications. Conclusion: Leukopenia commonly occurred posttransplant and was associated with modifiable and non-modifiable pretransplant factors.